The Impact of Income Inequality and Energy Consumption Dynamics on Environmental Degradation in Indonesia - S, Ririt Iriani Sri; Islamudin, Ardhi; P, Ni Putu Rekha; Jaenudin, M; Imamah , Fauziyah (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
Climate change as a form of environmental degradation is an important issue that needs to be addressed to achieve the SDGs. The aim of this research is to analyze the influence of economic growth, energy consumption, income inequality on environmental degradation in Indonesia in the long term and short term and to analyze the suitability of the hypothesis Environmental Kuznets Curve (EKC) is theoretically proven and valid in Indonesia both in the long term and short term. Researchers focus on research in Indonesia because Indonesia is a developing country with significant economic growth, but often there is intensive exploitation of natural resources. The data used in this research is time series data year 1991-2020. In this research, Error Correction Model (ECM) is used to see the influence of independent variables on the dependent variable in the long term and short term, as well as to test hypotheses Environmental Kuznets Curve (EKC), the hypothesis which states there is a relationship between economic growth and environmental quality and depicts an inverted curve is tested using the program Eviews 12. The results of this research are that the economic growth variable has no effect on environmental degradation in Indonesia in the short term, but in the long term economic growth has a significant positive effect on environmental degradation. The energy consumption variable has a positive and significant influence on environmental degradation in Indonesia both in the short and long term. The income inequality variable has no effect on environmental degradation in Indonesia in both the short and long term, there is a negative effect but it is not significant. Environmental Kuznets Curve (EKC) in Indonesia is in accordance with the existing EKC hypothesis. The government needs to implement sustainable development policies and green technology to reduce the negative impact of economic growth and energy consumption on the environment.